THE CATEGORY OF EVALUATION IN POLITICAL DISCOURSE - Tatiana Ananko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
Political discourse is a popular area of research because it penetrates a modern society. Being usually delivered by politicians, political discourse is a complex linguistic phenomenon which is directly or indirectly aimed at distributing, exercising the political power and winning the majority of votes during elections. This article deals with the category of evaluation which is considered to be a semantic and pragmatic category and can be one of the most powerful means of influence on the audience. This study focuses on the evaluative means used by Hillary Clinton as one of the presidential candidates in the USA in her speeches during the presidential campaign. Under the Appraisal theory framework, this paper discusses a variety of meaning-making resources used by the speaker to express her evaluative involvement in communication. The categories of engagement and graduation are also analysed. The attention is also paid to the interrelations between evaluation and values. Of special interest is a wide use of metaphors as well as the semantic polarisation of evaluative components in the speeches of the politician. The results show that the attitudinal meanings are mostly conveyed by judgements.